Detection of cortical activation and effective connectivity using Dynamic Causal Modelling through functional magnetic resonance imaging - Narayanan, Vandhana; B., Ragini (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/